PERBEDAAN KONSUMSI RITUAL AGAMA HINDU SEBELUM DAN SAAT COVID-19 DI KOTA DENPASAR - Karmini, Ni Luh; Sutrisna, I Ketut (Buletin Studi Ekonomi, 2023)
Covid-19 affects the income received by the community because the world economy is experiencing a recession due to restrictions on economic activities. Covid-19 does not reduce the activities of the Balinese people, especially the Balinese Hindu community, in carrying out religious ceremonies. Ritual consumption issued by the Balinese Hindu community, one of which is in the form of expenditure for piodalan sanggah (family temple) which is routinely carried out every six months based on Balinese calendar calculations. This study aims to determine the differences in the consumption of Hindu religious rituals before and during Covid-19, as well as the factors that influence the consumption of Hindu religious rituals. Differences in ritual consumption before and during covid will be tested using the Wilcoxon method. The sample used is 30 respondents who live in Denpasar City. The results showed that there were differences in piodalan consumption before and during the COVID-19 pandemic. The factors that determine ritual consumption are the living environment, family habits, income, determined by the offerings and determined by the stakeholders. according to the Vedas is not just following customs or customs.